Community-based participatory approach for development: Implementation manual - Oduor, Francis; Induli, Irene; Aluso, Lillian; Jordan, Irmgard; Termote, Celine (2024)
This manual was developed by Bioversity International with the intention to develop nutrition sensitive interventions to improve diets. The manual is based on participatory workshops in Vihiga, Busia, and Turkana counties, Western and North-Western Kenya. The manual is presented in the form of six workshops, with all the instructions needed to replicate each of the workshops. It is intended as a generic guide — rather than a blueprint of every workshop detail — and requires adaptation to the specific context you want to apply it in. Just as field staff should design their program activities considering the capabilities and needs of the communities they serve, so should one using this manual view it as a guide to be adapted to local contexts and priorities. The manual describes the procedure to be followed in detail, according to the steps that were taken in each of the six workshops. This part targets program leaders and is in particular useful for researchers, desk, and field workers. The Alliance of Bioversity International and CIAT has carried out this type of workshops in participatory intervention development research in the context of nutrition and restoration. The details are included in the annex.